2012
DOI: 10.1007/s11255-012-0209-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemodialysis session on the dynamics of carnitine ester profile changes in l-carnitine pretreated end-stage renal disease patients

Abstract: The washout induced by HD session results in variable depletion of short-, medium-, and long-chain carnitine esters in carnitine-pretreated patients; the recovery of the circulating carnitine esters from the body stores occurs within 30 min after the cessation of the HD procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Next, we calculated the removal rate of long‐chain acylcarnitine, adjusting for total protein levels before and after dialysis. We found that, similarly to previous reports, the removal rate of long‐chain acylcarnitine was lower than that of short‐chain or medium‐chain acylcarnitines, The reason for this is considered to be because long‐chain acylcarnitines have greater molecular weight and lipophilicity. However, in all patients in the present study, haemodialysis or haemodiafiltration using a high performance membrane with high β2MG (molecular weight: 11800) clearance was used.…”
Section: Discussionsupporting
confidence: 88%
“…Next, we calculated the removal rate of long‐chain acylcarnitine, adjusting for total protein levels before and after dialysis. We found that, similarly to previous reports, the removal rate of long‐chain acylcarnitine was lower than that of short‐chain or medium‐chain acylcarnitines, The reason for this is considered to be because long‐chain acylcarnitines have greater molecular weight and lipophilicity. However, in all patients in the present study, haemodialysis or haemodiafiltration using a high performance membrane with high β2MG (molecular weight: 11800) clearance was used.…”
Section: Discussionsupporting
confidence: 88%
“…5 We found that Fc and Tc levels in non-medicated patients undergoing HD were lower than those in the control group. Patients may have low Tc and Fc levels due to lower protein and meat intake, which results in lower carnitine intake; less absorption by the gastrointestinal tract; reduced carnitine synthesis in the kidneys; low renal tubular reabsorption; carnitine transport disorder; and the fact that it is highly dialyzable because of its low molecular weight and lack of protein binding in the plasma.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, the potential role of uridine 5-diphosphate in the inflammatory response is likely to be related to the involvement of chemokines in inflammation. The depletion of carnitine was previously reported to be prevalent in hemodialysis patients, which was assumed to be associated with their inflammatory response in patients [36]. Moreover, exogenous carnitine was required to satisfy energy consumption, which might reflect on carnitine's indirect modulation of the inflammatory response by regulating energy metabolism.…”
Section: Discussionmentioning
confidence: 99%